Future of Corporation: Partnership of Owners and Staff - BELOBOKOV, Andrey J.; LIHTZINDER, Boris J.; IVANOVA, Ludmila B. (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
As a model of corporate development we suggest the model of transformation of corporation into partnership of the owner and the staff, which is the partnership of the production means holder (owner) and the corporate structure (management and staff). We considered the transformation of corporation into partnership on the relationship of lease, as well as the elements, forming simulation model of transformation of corporation into partnership. We also showed the terms when the possibility of corporate development on the basis of partnership of owners and staff is preferable. The authors analyzed the scheme of transformation of corporations with majoritarian state participation into Partnership.
Keywords: management structure, corporation, corporate development, partnership, common impartial property, self-management, business operator, management, investor, lease, simulation model